Gender Aspect of Studying Social Visibility of One's Own Body Image - I V Groshev; T Yu Shtyrkina (Peoples' Friendship University of Russia (RUDN University), 2012)
The article is devoted to the research of social visibility of one's own body image in the gender aspect. The components of their own body image in girls and young men and also the impact of the psychological and social factors on the perception of gender image are estimated in the comparative aspect.